Utility of extended HPV genotyping for the triage of self-sampled HPV-positive women in a screen-and-treat strategy for cervical cancer prevention in Cameroon: a prospective study of diagnostic accuracy - Pierre Vassilakos; Evelyn Tincho; Bruno Kenfack; Patrick Petignat; Ania Wisniak; Celine Broquet; François Marcel Ndam Nsangou; Michel Noubom; Emilien Jeannot (BMJ Open)
Objective To explore the utility of extended Human Papillomavirus (HPV) genotyping to detect cervical intraepithelial neoplasia grade 2 or more (CIN2+) in a ‘screen-and-treat’ strategy for HPV-positive women in low-resource settings.Design Prospective study of diagnostic accuracy.Setting The study took place in West Cameroon between September 2018 and March 2020.Participants 2014 women were recruited. Asymptomatic, non-pregnant women aged 30–49 years without history of CIN treatment, anogenital cancer or hysterectomy were eligible.Interventions Participants performed self-sampling for HPV testing with GeneXpert followed by visual inspection with acetic acid and Lugol’s iodine (VIA) triage before treatment if required.Main outcome measures Liquid-based cytology, biopsies and endocervical brushing were performed in HPV-positive women as quality control. We assessed the detection rate of CIN2+ by HPV genotyping (two pools of genotypes obtained from the Xpert system, pool_1 (HPV 16, 18, 45) and pool_2 (HPV 16, 18, 45, 31, 33, 35, 52, 58)), VIA and cytology.Results 382 (18.2%) women were HPV-positive among which 11.5% (n=44) were CIN2+. Of those 44 participants, 41 were triaged positive by extended genotyping, versus 35 by VIA and 33 by cytology. Overall, triage positivity was of 68.4% for extended genotyping, 59.3% for VIA and 14.8% for cytology, with false positive rates of 83.4%, 84.1% and 37.7%, respectively. Extended genotyping had a higher sensitivity for CIN2+ detection (93.2%, CI: 81.3 to 98.6) than VIA (79.5%, CI: 64.7 to 90.2, p=0.034) and cytology (75.0%, CI: 59.7 to 86.8, p=0.005). No significant difference was observed in the overtreatment rate in triaged women by extended genotyping or VIA (9.9%, CI: 8.6 to 11.3, and 8.8%, CI: 7.7 to 10.1), with a ratio of 6.0 and 6.3 women treated per CIN2+ diagnosed.Conclusion Triage of HPV-positive women with extended HPV genotyping improves CIN2+ detection compared with VIA with a minor loss of specificity and could be used to optimize the management of HPV-positive women.Trial registration number NCT03757299.